How the Digital Endorsement Campaign Affects Student’s Attitude towards a Cinema Theater Brand: The Case of #JajanAsyikXXI on Instagram - Wahyuni Pudjiastuti; Qisti Qasthari (Jobmark: Journal of Branding and Marketing Communication, 2024)
The rapid number of social media users and changes in consumer behavior today requires marketers to adapt quickly. The use of celebrity endorser "Titan Tyra" in the #JajanAsikDiXXI campaign on Instagram is one of XXI's digital promotional activities. This study measures the effect of celebrity endorser characteristics "Titan Tyra" in the #JajanAsikdiXXI campaign on the attitudes of Communication Science students at Bakrie University toward the XXI brand. This research uses a quantitative approach with an explanatory case study method. The data was collected using questionnaires, observation, tracing professional documents, and digital documentation. The distribution of questionnaires was carried out to 86 active students of Communication Science at Bakrie University using cluster random sampling where the clusters used were classes from each course that took place in the even semester of 2019/2020. The results showed that all the characteristics of celebrity endorsers attached to Titan Tyra had a significant and simultaneous influence on the attitudes of active students of Communication Science at Bakrie University towards the XXI brand. This research is worthwhile to provide insight to marketers about promotional activities using celebrity endorsers to increase positive brand attitudes.